Application of system analysis in scientific research in the field of sports - Ж.Л. Козина; Е.А. Репко; С.В. Козин; М.З. Цеслицка; Р.К. Мушкета (H.S. Skovoroda Kharkiv National Pedagogical University, 2017)
The aim of the work was to determine the algorithm for system analysis of the individualization of the process of training athletes on the basis of common natural-scientific laws in nature. Material and methods. Methods of research: theoretical analysis of literary data, methods of pedagogical testing, pedagogical experiment, physiological, biochemical, psychophysiological methods of research, methods of mathematical statistics. Results. It is shown that the creation of effective individual training programs for athletes requires the use of a system analysis of various aspects of the functioning of the organism. The basic laws of development of an athlete or team repeat the general patterns of development of complex systems in animate and inanimate nature. For the analysis of the athlete as a system and the creation of individual training programs, it is necessary to rely on the structure of preparedness and regularity of the dynamics of gaming performance. Conclusions. The use of individual training programs in combination with universal methods of individualization increases the effectiveness of competitive activities.